Reading Strategies in Acquisition of Vocabulary of Professions - Axmatovich, Elchayev Zohidjon (International Journal on Integrated Education, 2023)
In studying written contexts in a variety of professions, learners have to know and follow the strategies for reading comprehension. Reading comprehension requires learners a lot of fundamental knowledge such as grammar and vocabulary because without being familiar with terminology of any field it is impossible to perceive the meaning of the words as well as their functions in the sentence construction. Furthermore, we carried out deep-ended analysis in reading comprehension, stating some short-professionally-oriented contexts.